Evaluation of antibacterial activity from flowering plants and optimization of process conditions for the extraction of antibacterial compounds from Spathiphyllum Cannifolium leaves - Abdullah, Erlina; Ahmad Raus, Raha; Jamal, Parveen (Academic Journals, 2011)
The screening practices for phytochemical compound from plants is essential to explore more natural sources to replace synthetic antibiotics which generally associated with multi-drug resistance as well as having side effects such as hypersensitivity, immune-suppression and allergic reactions. In this study, screening of antibacterial property from 19 Malaysian flowering plants was conducted and optimization of the process conditions for extraction of antibacterial compounds was carried out as well. During the screening, the plants were extracted with methanol, ethyl acetate, hexane and distilled water, individually at concentration of 0.1g/ml for 10 hours at room temperature and agitated at 300 rpm. The crude extracts of each plant (5 mg/disc) were tested against Bacillus subtilis and Escherichia coli using agar disc diffusion assay method. The optimization study was carried out as designed by Central Composite Design (CCD) using Design Expert 6.0.8 software and the parameters that were considered for optimization include agitation, temperature, and incubation time. The screening results showed most of the plant samples extracted with methanol and ethyl acetate, have indicated positive activity toward B. subtilis growth but not E. coli. Ethyl acetate extract of Spathiphyllum cannifolium leaves showed the highest antibacterial activity and optimization of extraction for antibacterial compound was carried out using this plant. The best conditions postulated from optimization study are 10hours, 300rpm, and 30⁰C. Analysis of Variance (ANOVA) of this study demonstrated that both temperature and speed factor significantly (p< 0.05) affects the extraction process. In conclusion, this study suggested S. cannifolium is a highly potential plant to be considered for development of new antibiotic and the optimum extraction process conditions obtained from this study are useful for efficient extraction of antibacterial compounds.